Integrasi Paradigma Akuntansi: Refleksi atas Pendekatan Sosiologi dalam Ilmu Akuntansi - Mulawarman, Aji Dedi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The purpose of this article is to perform reflection of accounting science in paradigmatic domain. Choice of accounting paradigm in this article is agreed in term of accounting science integration stance, not in accounting science war stance. Science integration is carried out by sociological metatheorizing on accounting in three ways. First, metatheorizing as a means of attaining a better and deeper understanding of accounting theory and or accounting science.Â Second, metatheorizing as a prelude discource forms to develop new accounting theories and or accounting sciences. Third, metatheorizing is conducted as a source that underlies accounting science of overarching new perspective or paradigm in accounting.